Pengaruh Penambahan Nutrient (NPK dan Pupuk Urea) terhadap Bioethanol Hasil Fermentasi Biji Alpukat (Persea americana Mill.) - Zakyya Septiana Putri; Aceng Ruyani; Mellyta Uliyandari; Rendy Wikrama Wardana; A. A. Sukarso (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Bioethanol is an energy source obtained through fermentation. In bioethanol production, Persea americana seeds are used as a fermentation medium because they contain lots of carbohydrates. This research aims to determine the effect of additional nutrients (NPK and urea fertilizer) required by Saccharomyces cerevisiae by varying the nutritional variables in the form of NPK and urea fertilizer. The process of making bioethanol goes through stages: making Persea americana seed flour, hydrolysis process using 6% HCl, then fermentation process, and distillation process. This research was carried out with the addition of Nutrients in the form of NPK and Urea Fertilizer with 5 treatments, namely: A) 100% yeast (no addition of Nutrients); B) 100% NPK (4 g); C) 100% Urea Fertilizer (4 g); D) 50% NPK and 50% Urea Fertilizer (4 g NPK and 4 g Urea Fertilizer); and E) 75% NPK and 25% Urea Fertilizer (3 g NPK and 1 g Urea Fertilizer), and varying the length of fermentation time to 13, 19, and 25 days. Success parameters are assessed through the bioethanol yield produced by each treatment. The research results showed that the highest bioethanol (29.7 ± 0.47%) was composition E (NPK 75% and Urea Fertilizer 25%) with a fermentation time of 25 days.